A Study on Status of Farm Power and Scope of Farm Mechanization in the Agro-Climatic Zone of Chhattisgarh Plains - Chandraker, A. K.; Victor, V. M.; Khalkho, D. (Prabandhan: Indian Journal of Management, 2015)
An investigation was carried out to know the status of farm mechanization in Chhattisgarh plains. A survey conducted in eight villages of the agro-climatic zone of Chhattisgarh state revealed that the average percentage share of tractive power, stationary power, and draught animal power, & cropping intensity and irrigation intensity of Chhattisgarh plains was 49.32 (0.43 kW/ha),15.55(0.12 kW/ha), and 33.59(0.28 kW/ha), & 164.77 and 64.77 respectively of cultivable area. Average farm power availability and land holding per family in Chhattisgarh plains was 0.84 kW/ha and 2.18 ha respectively. Average farm power availability of the selected villages was found to be less than the national average (1.6 kW/ha). The study revealed that the villages had sufficient draught animals, indigenous implements, and hand tools like indigenous plough, biasi plough, kopar, patela, pick-axe, crowbar, spade, wooden mallet, and so forth. The study indicated a dire need of increasing farm power availability and farm mechanization in this agro-climatic zone to increase the productivity of the land.